Sulforaphane: An emergent anti-cancer stem cell agent - Coutinho, Leandro de Lima; Junior, Tharcísio Citrangulo Tortelli; Rangel, Maria Cristina (Frontiers in Oncology, 2023)
Cancer is a major public health concern worldwide responsible for high morbidity and mortality rates. Alternative therapies have been extensively investigated, and plant-derived compounds have caught the attention of the scientific community due to their chemopreventive and anticancer effects. Sulforaphane (SFN) is one of these naturally occurring agents, and studies have shown that it is able to target a specific cancer cell population displaying stem-like properties, known as cancer stem cells (CSCs). These cells can self-renewal and differentiate to form highly heterogeneous tumor masses. Notably, most of the conventional chemotherapeutic agents cannot target CSCs once they usually exist in a quiescent state and overall, the available cytotoxic drugs focus on highly dividing cells. This is, at least in part, one of the reasons why some oncologic patients relapse after standard therapy. In this review we bring together studies supporting not only the chemopreventive and anticancer properties of SFN, but especially the emerging anti-CSCs effects of this natural product and its potential to be used with conventional antineoplastic drugs in the clinical setting.